Family influences on career decisions by black first-year UKZN students - Mhlongo, Ziphozethu; O’Neill, Vivien (South African Journal of Higher Education, 2016)
The attainment of democracy in South Africa brought many previously disadvantaged families new hope and promise for enhanced entry to higher education. However, as these opportunities continue to grow, this research study asked whether these students are ready to make effective use of their expanded prospects. This qualitative study was informed by the Interactive Model of Career Decision-Making. It focused on family and community influences in tertiary educational career decision-making with special reference to black South African students’ context of historical disadvantage. Family and community variables such as socio-economic status, culture, parental influence, family composition and support were investigated. Thematic analysis indicated strong links between family socio-economic status and student career decisions. Familial support further emerged as an important factor when students make career decisions.